Superhumanity : design of the self - Axel, Nick; Colomina, Beatriz; Hirsch, Nikolaus; Vidokle, Anton; Wigley, Mark (Eflux Architecture : University of Minnesota Press : The Graham Foundation, 2018)
A wide-ranging and challenging exploration of design and how it engages with the self. The field of design has radically expanded. As a practice, design is no longer limited to the world of material objects but rather extends from carefully crafted individual styles and online identities to the surrounding galaxies of personal devices, new materials, interfaces, networks, systems, infrastructures, data, chemicals, organisms, and genetic codes. Superhumanity seeks to explore and challenge our understanding of "design" by engaging with and departing from the concept of the "self." This volume brings together more than fifty essays by leading scientists, artists, architects, designers, philosophers, historians, archaeologists, and anthropologists, originally disseminated online via e-flux Architecture between September 2016 and February 2017 on the invitation of the Third Istanbul Design Biennial. Probing the idea that we are and always have been continuously reshaped by the artifacts we shape, this book asks: Who designed the lives we live today? What are the forms of life we inhabit, and what new forms are currently being designed? Where are the sites, and what are the techniques, to design others? This vital and far-reaching collection of essays and images seeks to explore and reflect on the ways in which both the concept and practice of design are operative well beyond tangible objects, expanding into the depths of self and forms of life